Boudicca : a novel - Cast, P. C. (William Morrow, an imprint of HarperCollins Publishers, 2025)
In Roman-occupied Britain, the Iceni tribe crowns an extraordinary new queen. Tall and flame-haired, Boudicca is devoted to Andraste, the Iceni's patron goddess, known for her raven familiar, her fierceness and her swirling blue tattoos. Boudicca and her two young daughters will carry the tribe forward in dangerous times. Roman tax collector Catus Decianus, expecting weakness in a female ruler, launches a devastating attack on the tribe's stronghold. Boudicca and her family barely survive--but they refuse to bend the knee. She calls a war council, bringing together her most trustworthy allies, including her childhood friend Rhan, now a powerful Druid seer, and the horse master Maldwyn, whose devotion to Boudicca runs deeper than a warrior to a queen. Surprising the Romans, Boudicca's armies sack the wealthy cities of Camulodunum, Londinium and Veralamium. As the snow falls, the Celts retreat to a hidden valley to plot their assault on the remaining Roman legions, determined to force the invaders from Britain. But in the jagged ice of winter the Druid Rhan foresees a tragic end to Boudicca's rebellion. Although the defeat of the Iceni is spelled out in signs sent by the gods, Rhan swears she will alter the future and save her queen. Now the battle-hardened Boudicca must put her trust in the powers of the otherworld to save her from both the traitors in her midst and from Rome's mighty legions.